The economic world view studies in the ontology of economics - Mäki, Uskali (Cambridge University Press, 2001)
The beliefs of economists are not solely determined by empirical evidence in direct relation to the theories and models they hold. Economists hold 'ontological presuppositions', fundamental ideas about the nature of being which direct their thinking about economic behaviour. In this volume, leading philosophers and economists examine these hidden presuppositions, searching for a 'world view' of economics. What properties are attributed to human individuals in economic theories, and which are excluded? Does economic man exist? Do markets have an essence? Do macroeconomic aggregates exist? Is the economy a mechanism, the functioning of which is governed by a limited set of distinct causes? What are the methodological implications of different ontological starting points? This collection, which establishes economic ontology as a coordinated field of study, will be of great value to economists and philosophers of social sciences